Bioinformatic identification of COLEC12 as a diagnostic biomarker and risk factor in pediatric FSGS - Gao, Lei; Yang, Zhenkun; Yang, Yongbing; Wang, Jingjing; Dong, Wenyan (Frontiers in Pediatrics, 2025)
BackgroundIn children, focal and segmental glomerulosclerosis (FSGS) and minimal change disease (MCD) have a similar appearance on electron microscopy, making them indistinguishable in clinical diagnosis. Here, we conducted genomic screening to identify a biomarker for the differential diagnosis and assess its clinical implications in pediatric FSGS.MethodsIn the study, cohorts from public databases were analyzed through informatics analysis. First, molecular characteristics were analyzed using Gene Set Enrichment Analysis (GSEA) and Gene Ontology (GO) annotation, and Xcell was used to evaluate the infiltration of immune cells. Next, diagnostic and differentially diagnostic values of candidate biomarkers were studied using Receiver Operating Characteristic (ROC) curve analysis. Simultaneously, the clinical significance of the biomarker was analyzed in pediatric FSGS.ResultsCompared to the healthy population, There were 27 genes significantly up-regulated and 129 genes significantly down-regulated in FSGS patients, which related to immune response and cell apoptosis. In FSGS, the T helper (Th) effector memory cell and macrophage M2 cell were significantly highly infiltrated. Meanwhile, regulatory T cells (Tregs) and plasma B cells showed a significant decrease. COLEC12 is the most different gene between FSGS and MCD, and had high value in the diagnosis and differential diagnosis of FSGS. In pediatric FSGS, COLEC12 expression is associated with poor prognosis.ConclusionFSGS is intricately linked with immune responses. COLEC12 is a risk factor for FSGS in children and a candidate marker for FSGS diagnosis.